A novel bioactive nerve conduit for the repair of peripheral nerve injury - Li, Bin-bin; Yin, Yi-xia; Yan, Qiong-jiao; Wang, Xin-yu; Li, Shi-pu (Neural regeneration research, 2016)
The use of a nerve conduit provides an opportunity to regulate cytokines, growth factors and neurotrophins in peripheral nerve regeneration and avoid autograft defects. We constructed a poly-D-L-lactide（PDLLA）-based nerve conduit that was modified using poly{（lactic acid）-co-[（glycolic acid）-alt-（L-lysine）]} and β-tricalcium phosphate. The effectiveness of this bioactive PDLLA-based nerve conduit was compared to that of PDLLA-only conduit in the nerve regeneration following a 10-mm sciatic nerve injury in rats. We observed the nerve morphology in the early period of regeneration, 35 days post injury, using hematoxylin-eosin and methylene blue staining. Compared with the PDLLA conduit, the nerve fibers in the PDLLA-based bioactive nerve conduit were thicker and more regular in size. Muscle fibers in the soleus muscle had greater diameters in the PDLLA bioactive group than in the PDLLA only group. The PDLLA-based bioactive nerve conduit is a promising strategy for repair after sciatic nerve injury.